(untitled) (Texas Journal of Engineering and Technology, 2022)
The article examines the opinions of the world’s leading scientists on the peculiarities of the development and management of projects related to the creation of renewable energy resources, the specific characteristics of the development and management of projects related to the creation of renewable energy resources, The growth trend of renewable energy sources in the world in 2014-2020 was analyzed, the experiences of developed countries were analyzed and compared, and justified conclusions and proposals were developed regarding the specific features of the development and management of projects related to the creation of renewable energy resources. and recommendations for use in our country are given.